2017
DOI: 10.1515/cclm-2016-0566
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and clinical validation of the new Abbot Architect 25(OH)D assay: fit for purpose?

Abstract: This modified version of the Abbott Architect assay is clearly improved compared to the previous one and presents a better agreement with the LC-MS/MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Blood samples were drawn after at least a 4-h fast and stored at − 80 °C. Serum 25-hydroxyvitamin D, which is the circulating biomarker of vitamin D status, was analyzed between 2016 and 2018 at the University Medical Center Hamburg-Eppendorf (Hamburg, Germany) within the frame of the European BiomarCaRE project (Biomarkers for Cardiovascular Risk Assessment in Europe) [19] and measured using a one-step immunoassay on the Abbott Architect i2000 (Abbott Laboratories, Abbott Park, IL, USA) [20]. The valid measurement range was 8-160 ng/mL.…”
Section: Assessment Of Vitamin D Concentrationsmentioning
confidence: 99%
“…Blood samples were drawn after at least a 4-h fast and stored at − 80 °C. Serum 25-hydroxyvitamin D, which is the circulating biomarker of vitamin D status, was analyzed between 2016 and 2018 at the University Medical Center Hamburg-Eppendorf (Hamburg, Germany) within the frame of the European BiomarCaRE project (Biomarkers for Cardiovascular Risk Assessment in Europe) [19] and measured using a one-step immunoassay on the Abbott Architect i2000 (Abbott Laboratories, Abbott Park, IL, USA) [20]. The valid measurement range was 8-160 ng/mL.…”
Section: Assessment Of Vitamin D Concentrationsmentioning
confidence: 99%
“…As the sources of lead exposure have decreased (leaded gasoline and paint), so too has the number of children presenting with increased blood lead concentrations. The most recent CDC guidelines state that blood lead concentrations ≥5 μg/dL are considered increased, and in 2015 only 3% of US children <72 months of age had lead concentrations ≥5 μg/dL (3).…”
Section: To the Editormentioning
confidence: 99%
“…As the ease of quantifying blood lead has increased and median concentrations have decreased, the use of ZPP as a screen for lead toxicity has become unnecessary according to the most recent CDC guidelines (3). Despite these recommendations, we continued to receive requests for ZPP and lead…”
Section: To the Editormentioning
confidence: 99%
“…Various analytical evaluations related to CV and bias have been published in previous studies in the literature [12][13][14]. Cavalier et al [16] reported within-run and between-run CV values of 10.9-13.3% and 1. .0-3.5%, respectively, and within-run, between-run, and between-day CV% values of the Beckman Coulter Access 25(OH)D Total test at concentrations of 21.5±6.5 ng/mL and 45.0±10 ng/mL in the Access2 System were 6.7-6.1% and 13.9-5.6%, respectively.…”
Section: Resultsmentioning
confidence: 99%